2023
DOI: 10.1111/jpc.16323
|View full text |Cite
|
Sign up to set email alerts
|

Randomised controlled trial of melatonin for paediatric functional abdominal pain disorders

Abstract: Aim Melatonin seems to have a positive impact on the brain–gut axis and many direct and indirect effects on the gastrointestinal tract. This trial aimed at assessing the efficacy of melatonin combined with Lactobacillus Rhamnosus GG given in the treatment of paediatric patients with functional abdominal pain disorders. Methods Forty‐two patients aged 4–18 years old who fulfilled the Rome IV Diagnostic Criteria for functional abdominal pain disorders were enrolled. Melatonin 3 or 5 mg in combination with Lactob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…The participants were randomized to treatment with the combination of melatonin and L. Rhamnosus GG or placebo in combination with L. Rhamnosus GG for 4 weeks and the primary endpoint was defined as at least a 50% reduction in the abdominal pain index (API) at 12 weeks. There was a significant improvement in API with the treatment combination of melatonin and L. Rhamnosus GG without any adverse events [18 ▪ ]. The authors endorse that a larger study is warranted and could address their limitations of being a small single-center trial.…”
Section: Treatment and Managementmentioning
confidence: 90%
“…The participants were randomized to treatment with the combination of melatonin and L. Rhamnosus GG or placebo in combination with L. Rhamnosus GG for 4 weeks and the primary endpoint was defined as at least a 50% reduction in the abdominal pain index (API) at 12 weeks. There was a significant improvement in API with the treatment combination of melatonin and L. Rhamnosus GG without any adverse events [18 ▪ ]. The authors endorse that a larger study is warranted and could address their limitations of being a small single-center trial.…”
Section: Treatment and Managementmentioning
confidence: 90%
“…This statement was later used as evidence that several Lactobacillus produce melatonin. For example, in a trial on abdominal pain in children, Lactobacillus and exogenous melatonin were used for the health of the patient [ 101 ], as if melatonin produced by Lactobacillus was not enough to obtain the desired effect. In another study, melatonin was shown to increase the amount of Lactobacillus previously decreased by sleep deprivation as if the production of melatonin by Lactobacillus was not enough to counterbalance the decrease in circulating melatonin [ 102 ].…”
Section: Some Proposed Mechanisms Behind the Claimed Beneficial Effec...mentioning
confidence: 99%